2022
DOI: 10.1038/s41419-022-05214-9
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of MCL-1 in breast cancer-associated fibroblasts reverses their myofibroblastic phenotype and pro-invasive properties

Abstract: Cancer-associated fibroblasts (CAF) are a major cellular component of epithelial tumors. In breast cancers in particular these stromal cells have numerous tumorigenic effects in part due to their acquisition of a myofibroblastic phenotype. Breast CAFs (bCAFs) typically express MCL-1. We show here that pharmacological inhibition or knock down of this regulator of mitochondrial integrity in primary bCAFs directly derived from human samples mitigates myofibroblastic features. This decreases expression of genes in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Bonneaud and colleagues unraveled that targeting MCL-1 via BH3 mimetic, an antagonist to various BCL-2 congeners, including MCL-1, can mitigate the invasion of cancer cells and inhibit their tumor-promoting function. A possible mechanism is that BH3 mimetic promotes mitochondrial cleavage in bCAF [ 286 ]. Exosome-based research is in full swing, and exosome-based nucleic acid delivery has become an emerging cancer treatment option [ 287 ].…”
Section: Background Knowledge Of Cafsmentioning
confidence: 99%
“…Bonneaud and colleagues unraveled that targeting MCL-1 via BH3 mimetic, an antagonist to various BCL-2 congeners, including MCL-1, can mitigate the invasion of cancer cells and inhibit their tumor-promoting function. A possible mechanism is that BH3 mimetic promotes mitochondrial cleavage in bCAF [ 286 ]. Exosome-based research is in full swing, and exosome-based nucleic acid delivery has become an emerging cancer treatment option [ 287 ].…”
Section: Background Knowledge Of Cafsmentioning
confidence: 99%
“…A promising strategy for targeting the protumoral effects of CAFs is to reverse their 'activated' phenotype. We have shown that targeting MCL-1 in CAFs attenuates their myofibroblastic phenotype, including a reduction in their pro-invasive capacity 36 . In our study, CAFs protect BCL-xL deficient cancer cells against chemotherapy independently of their own sensitivity to treatments, which is heterogeneous.…”
Section: Discussionmentioning
confidence: 95%
“…breast cancer, colon cancer, multiple myeloma). Existing evidences shows that MCL-1 is closely related to tumorigenesis, immortalization, recurrence, and therapeutic resistance [44][45][46]. Martina et al found that the Mcl-1 gene is necessary for senescent tumor cell proliferation and metastatic dissemination using single-cell RNA-sequencing analysis [47].…”
Section: Discussionmentioning
confidence: 99%